2013
DOI: 10.1371/journal.pone.0061088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-Seq and Microarray Analysis of Gene Expression Changes in B-Cell Lymphomas of Canis familiaris

Abstract: Comparative oncology is a developing research discipline that is being used to assist our understanding of human neoplastic diseases. Companion canines are a preferred animal oncology model due to spontaneous tumor development and similarity to human disease at the pathophysiological level. We use a paired RNA sequencing (RNA-Seq)/microarray analysis of a set of four normal canine lymph nodes and ten canine lymphoma fine needle aspirates to identify technical biases and variation between the technologies and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 62 publications
1
41
0
2
Order By: Relevance
“…The only exception was a higher transcription of parents in pollen relative to seedlings in RNA sequencing (mean and quantile 1 samples; absent in the quantile 4 sample), while the opposite results were obtained using microarrays ( Figures 3A and 3F). This difference is due to the higher sensitivity of RNA sequencing technology to quantify transcripts from lowly transcribed genes (Mooney et al, 2013;Zhao et al, 2014). This partially applies also to retrogenes, as the upregulation in pollen versus seedling is more pronounced in RNA sequencing compared with microarrays ( Figure 3F).…”
Section: Arabidopsis Retrogenes Are Transcribed In Male Gametesmentioning
confidence: 99%
“…The only exception was a higher transcription of parents in pollen relative to seedlings in RNA sequencing (mean and quantile 1 samples; absent in the quantile 4 sample), while the opposite results were obtained using microarrays ( Figures 3A and 3F). This difference is due to the higher sensitivity of RNA sequencing technology to quantify transcripts from lowly transcribed genes (Mooney et al, 2013;Zhao et al, 2014). This partially applies also to retrogenes, as the upregulation in pollen versus seedling is more pronounced in RNA sequencing compared with microarrays ( Figure 3F).…”
Section: Arabidopsis Retrogenes Are Transcribed In Male Gametesmentioning
confidence: 99%
“…However while microarray studies are instructive, they are being increasingly eclipsed by the utility of next generation high throughput sequencing (HTS) technologies [11]. Several studies have indicated that HTS technologies can determine gene expression level more accurately than microarrays [12,13], and also offer exciting insight into the transcript structures present under each condition studied [11,14,15]. The RpoN regulon of C. jejuni has been characterized by profiling the transcriptome of an rpoN mutant using HTS and compared to results previously obtained using microarray technologies [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published studies have compared data obtained from microarrays and RNA-seq in terms of technical reproducibility, variance structure, absolute expression and detection of DEGs or gene isoforms 820 (Supplementary Table 1). Some of these studies suggested that RNA-seq exhibits lower precision for weakly expressed genes owing to the nature of sampling 21, 22 , whereas others found higher sensitivity of RNA-seq for gene detection 23, 24 . The varied conclusions can be attributed to the fact that they used few treatment conditions and hence they do not cover a wide range of biologic complexity.…”
mentioning
confidence: 99%